Relações entre melhoria contínua e inovação de produtos e processos: estudo de múltiplos casos - Lizarelli, Fabiane Letícia (Universidade Federal de São Carlos, 2013)
Continuous Improvement (CI) and Innovation are important approaches to generate competitive advantage for organizations. These approaches need to be properly managed in order to ensure long-term results, and must be also aligned to the company's competitive strategies. Despite being seen as complementary approaches, they are often managed in completely independent ways. The literature shows the need for coexistence of CI and Innovation, especially in studies on continuous innovation and organizational ambidexterity. There is also a theoretical support that CI and Innovation should be aligned and have a collaborative role. However, there is a theoretical gap on the relationship between these two themes, is necessary to know what enables integration between Continuous Improvement and Innovation in organizations. Based on exploratory and systematic literature review, we identified the main relationships between CI and Innovation, six of them were studied. Were also identified practices and mechanisms that facilitate the existence of relationships in the company. Practices are dependent on interaction and collaboration between between people connected to CI and Innovation, therefore, were also identified integration mechanisms, related to organizational culture, knowledge management and organizational structure. A multiple case study was conducted. The chosen companies belong to different sectors and have Innovation and Continuous Improvement well developed. It was possible to identify at which level the six relationships are present in different companies. It was possible to identify which practices are more related to the high presence of relationships, and point integration mechanisms used for each relationship.
Keywords: Melhoria contínua; Inovação de produtos; Estudo de caso; Integração; Colaboração; Práticas; Integração; Continuous improvement; Innovation; Practices; Integration; ENGENHARIAS::ENGENHARIA DE PRODUCAO